2013
DOI: 10.5194/hessd-10-14391-2013
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Small farm dams: impact on river flows and sustainability in a context of climate change

Abstract: Abstract. The repetition of droughts in France has led to a growing demand for irrigation water and consequently to an increase in requests for the construction of small farm dams. Although such dams are small, their accumulation in a basin affects the river flows. In order to gain more insight into their impact, a small farm dam model was built and connected to a hydrometeorological model. Several scenarios with different volume capacity, filling catchment size and filling period were tested for such dams. Th… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 31 publications
2
16
0
Order By: Relevance
“…The modelling results of the present study support the assumption of Habets et al (2014) and Meigh (1995) of a notable infl uence of farm dams in dry years. Overestimation of runoff during the wet season was reduced after the implementation of the farm dam module, but was still present.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…The modelling results of the present study support the assumption of Habets et al (2014) and Meigh (1995) of a notable infl uence of farm dams in dry years. Overestimation of runoff during the wet season was reduced after the implementation of the farm dam module, but was still present.…”
Section: Discussionsupporting
confidence: 70%
“…A number of case studies have shown that smaller farm dams can affect the fl ow pattern of a basin. Habets et al (2014) revealed that accumulated water for irrigation is not available for runoff processes and reported a decrease in the outfl ow in presence of farm dams. Studies in South Africa confi rmed the infl uence of farm dams on fl ow patterns Mantel et al, 2010), particularly aff ecting the base fl ow.…”
Section: Discussionmentioning
confidence: 99%
“…Each bar corresponds to a different catchment. The estimations are from the following references: a: Gutteridge-Haskins-Davey (1987), b: Ockenden and Kotwicki (1982), c: Girard (1973), d: Cresswell (1991), e: Teoh (2003), f: Habets et al (2014), and g: Kennon (1966). Figure 1 shows that the impacts on annual flows are not constant from year to year but tend to be lower during the wet years and two times greater than the median impact 5 in the driest years.…”
Section: Evidence Of the Impacts Of Small Reservoirs On Hydrologymentioning
confidence: 99%
“…Rather, a global estimation of reservoirs and their characteristics may be approximated from simple rules of spatial extrapolation (cf. Habets et al (2014)). For instance, to estimate the inflow into the equivalent reservoir, it is necessary to determine the contributive catchment.…”
Section: Aggregate Representationmentioning
confidence: 99%
See 1 more Smart Citation